Affirmation of Traditional Rights and Indigenous Women's Knowledge on Post-Mining Livelihood in Dompak Island, Riau Islands - Sri Wahyuni; Rahma Syafitri; Nikodemus Niko; Zikri Raudhatul Ahsan (CV. Literasi Indonesia, 2023)
This research aims to understand the indigenous women's knowledge of post-mining livelihoods in Pulau Dompak and how that knowledge is neglected in decision-making by the government and mining companies. The research uses a qualitative approach with data collection techniques through interviews, observations, and document studies. The results show that indigenous women have extensive and profound knowledge about post-mining livelihoods based on their experiences and traditional knowledge. However, their knowledge is often disregarded in decision-making related to post-mining reclamation by the government and mining companies. Women's involvement in decision-making is also limited due to patriarchal social structures in indigenous communities. This research recommends the need for recognition and protection of the traditional rights of indigenous women in decision-making related to post-mining reclamation, as well as efforts to reduce gender disparities in decision-making involvement.